Perbandingan Ablasi Radiofrekuensi dengan Transplantasi Hati sebagai Terapi Kuratif pada Karsinoma Hepatoseluler Stadium Awal: Laporan Kasus Berbasis Bukti - Gunawan, Mikhael Fabian; Safira, Ranindita Amaida; Singh, Gurmeet; Kalista, Kemal Fariz (UI Scholars Hub, 2025)
Hepatocellular carcinoma (HCC) is the most common type of liver cancer and the second leading cause of cancer-related mortality worldwide. Liver transplantation is considered the definitive treatment for HCC; however, in Indonesia, adult liver transplantation is still rarely performed due to donor limitations and high costs. Radiofrequency ablation (RFA) has therefore become a preferred therapeutic option in the management of HCC. This report discuss about the survival and recurrence rates of HCC in patients treated with RFA compared with those undergoing liver transplantation. A literature search was conducted using the PubMed, Cochrane, Embase, and Scopus databases. Selected articles were screened according to the predefined clinical question as well as inclusion and exclusion criteria. Critical appraisal was performed based on the 2011 Oxford Centre for Evidence-Based Medicine framework, assessing validity, importance, and applicability. Critical appraisal was conducted on two selected articles. One study reported comparable survival rates between the two groups. However, overall, both articles demonstrated that liver transplantation was associated with higher survival rates and lower recurrence rates compared with RFA. In conclusion, survival outcomes are superior with liver transplantation compared with RFA. Nevertheless, RFA may be considered in the management of hepatocellular carcinoma as a bridging therapy to liver transplantation or in situations where liver transplantation is not available.